Conductive Materials for Healing Wounds: Their Incorporation in Electroactive Wound Dressings, Characterization, and Perspectives - Korupalli, Chiranjeevi; Li, Hui; Nguyen, Nhien; Mi, Fwu‐Long; Chang, Yen; Lin, Yu‐Jung; Sung, Hsing‐Wen (Advanced healthcare materials, 2021)
The use of conductive materials to promote the activity of electrically responsive cells is an effective means of accelerating wound healing. This article focuses on recent advancements in conductive materials, with emphasis on overviewing their incorporation with non‐conducting polymers to fabricate electroactive wound dressings. The characteristics of these electroactive dressings are deliberated, and the mechanisms on how they accelerate the wound healing process are discussed. Potential directions for the future development of electroactive wound dressings and their potential in monitoring the course of wound healing in vivo concomitantly are also proposed. In a skin wound that disrupts the epithelial barrier, the trans‐epithelial potential falls, establishing an endogenous electric current from the unwounded epidermis to the wound. The application of an electroactive wound dressing on top of the wound enables conduction and more effective distribution of the endogenous electric current, stimulating the migration of host cells, ultimately accelerating healing of the wound.